The Effects of Religious Attendance and Evangelical Identification on Media Perception and Political Knowledge. Issue 2 (15th March 2019) - Gaskins, Ben
Abstract: Scholars have shown that religious activity can prepare individuals for civic activity by endowing them with the skills and motivation to engage in politics. Others, however, assert that religious dogmatism may lead to disengagement with the secular world and politics more generally. These two perspectives have resulted in contradictory findings on a key aspect of civic ability: political knowledge. I argue that while religiosity may indeed increase individuals' engagement in a wide array of political activities, including some aspects of political knowledge, religious commitment decreases the ability to acquire accurate information about certain types of political facts. This argument is tested with a number of national surveys, and I find that while religion has a mixed effect on knowledge of general political structures and actors, it increases the perception of media hostility, which leads to lower levels of political knowledge about policy-specific surveillance information.